Library Liberec - Kousal, Radim (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
It is said that the difficulty with the project of the modern library consists of the coexistence of a bibliotheca and a mediatheca − the two worlds of a library, a library of the past and a library of the future. How do we solve this problem? One way is the universal design, which is able to absorbe both of those worlds of the library and at the same time to have the capacity to absorbe the fluctuation of the library’s program for the future.